Principles and practice of geriatric surgery - Rosenthal, Ronnie A.; Zenilman, Michael E.; Katlic, Mark R. 1951- (Springer, 2011)
"In the preface to this impressive and well-produced book, the editors state that their aim is not to describe a new surgical specialty, since most surgeons will soon need to be "geriatric surgeons," but to assemble a comprehensive account that will allow "all providers of healthcare to the elderly to understand the issues involved in choosing surgery as a treatment option for their patients." This is a useful book that deserves to do well. I hope that the editors and their publisher will have the stamina to make this the first of several editions, as it is clear that updated information about surgery in the elderly will be required to keep pace with this important field." NEJM Book Review